Sustainability Assessment and Engineering of Emerging Aircraft Technologies—Challenges, Methods and Tools - Pinheiro Melo, Sofia; Barke, Alexander; Cerdas, Felipe; Thies, Christian; Mennenga, Mark; Spengler, Thomas S.; Herrmann, Christoph (Sustainability, 2020)
Driven by concerns regarding the sustainability of aviation and the continued growth of air traffic, increasing interest is given to emerging aircraft technologies. Although new technologies, such as battery-electric propulsion systems, have the potential to minimise in-flight emissions and noise, environmental burdens are possibly shifted to other stages of the aircraft’s life cycle, and new socio-economic challenges may arise. Therefore, a life-cycle-oriented sustainability assessment is required to identify these hotspots and problem shifts and to derive recommendations for action for aircraft development at an early stage. This paper proposes a framework for the modelling and assessment of future aircraft technologies and provides an overview of the challenges and available methods and tools in this field. A structured search and screening process is used to determine which aspects of the proposed framework are already addressed in the scientific literature and in which areas research is still needed. For this purpose, a total of 66 related articles are identified and systematically analysed. Firstly, an overview of statistics of papers dealing with life-cycle-oriented analysis of conventional and emerging aircraft propulsion systems is given, classifying them according to the technologies considered, the sustainability dimensions and indicators investigated, and the assessment methods applied. Secondly, a detailed analysis of the articles is conducted to derive answers to the defined research questions. It illustrates that the assessment of environmental aspects of alternative fuels is a dominating research theme, while novel approaches that integrate socio-economic aspects and broaden the scope to battery-powered, fuel-cell-based, or hybrid-electric aircraft are emerging. It also provides insights by what extent future aviation technologies can contribute to more sustainable and energy-efficient aviation. The findings underline the need to harmonise existing methods into an integrated modelling and assessment approach that considers the specifics of upcoming technological developments in aviation.